Confirmation of the mantis shrimp Lysiosquilla maculata (Fabricius, 1793) (Crustacea, Stomatopoda, Lysiosquillidae) from Taiwan - Chang, Li Ming; Chiang, Pei-An; Chan, Tin-Yam (Zootaxa, 2025)
The presence of the mantis shrimp Lysiosquilla maculata (Fabricius, 1793) in Taiwanese water is verified with the collection of a large adult male of this species from the northern-most coast of Taiwan. This constitutes the first formal record of L. maculata from Taiwan. Three species of Lysiosquilla are now known in Taiwan and a key to these three species is provided.